Helicopter reconnaissance indicators sensitivity analysis based on machine learning - JIANG Xinyi, LOU Benchao, ZENG Weiping (Zhihui kongzhi yu fangzhen)
In order to meet the requirements of sensitivity analysis in the design of helicopter reconnaissance indicators, based on the logistic regression method in machine learning, the reconnaissance capability index system of helicopter system contribution evaluation is established. Firstly, the basic steps of sensitivity analysis of helicopter reconnaissance indicators based on machine learning are introduced. Secondly, sensitivity analysis of helicopter reconnaissance mission effectiveness is achieved through task planning, constructing indicator systems, collecting relevant data, evaluating effectiveness, and using machine learning algorithms for modeling and training. This study can provide reference for the sensitivity analysis of helicopter task efficiency and provide more scientific and reasonable support for the development and application of helicopters in the system.